Calcineurin/NFAT Activation-Dependence of Leptin Synthesis and Vascular Growth in Response to Mechanical Stretch - Soudani, Nadia; Ghantous, Crystal M.; Farhat, Zein; Shebaby, Wassim N.; Zibara, Kazem; Zeidan, Asad (Frontiers in Physiology, 2016)
Background and Aims- Hypertension and obesity are important risk factors of cardiovascular disease. They are both associated with high leptin levels and have been shown to promote vascular hypertrophy, through the RhoA/ROCK and ERK1/2 phosphorylation. Calcineurin/NFAT activation also induces vascular hypertrophy by upregulating various genes. This study aimed to decipher whether a crosstalk exists between the RhoA/ROCK pathway, Ca+2/calcineurin/NFAT pathway, and ERK1/2 phosphorylation in the process of mechanical stretch-induced vascular smooth muscle cell (VSMC) hypertrophy and leptin synthesis. Methods and Results- Rat portal vein (RPV) organ culture was used to investigate the effect of mechanical stretch and exogenous leptin (3.1 nM) on VSMC hypertrophy and leptin synthesis. Results showed that stretching the RPV significantly upregulated leptin secretion, mRNA and protein expression, which were inhibited by the calcium channel blocker nifedipine (10 μM), the selective calcineurin inhibitor FK506 (1 nM) and the ERK1/2 inhibitor PD98059 (1 μM). The transcription inhibitor actinomycin D (0.1M) and the translation inhibitor cycloheximide (1 mM) significantly decreased stretch-induced leptin protein expression. Mechanical stretch or leptin caused an increase in wet weight changes and protein synthesis, considered as hypertrophic markers, while they were inhibited by FK506 (0.1 nM; 1 nM). In addition, stretch or exogenous leptin significantly increased calcineurin activity and MCIP1 expression whereas leptin induced NFAT nuclear translocation in VSMCs. Moreover, in response to stretch or exogenous leptin, the Rho inhibitor C3 exoenzyme (30 ng/mL), the ROCK inhibitor Y-27632 (10 μM), and the actin depolymerization agents Latrunculin B (50 nM) and cytochalasin D (1 μM) reduced calcineurin activation and NFAT nuclear translocation. ERK1/2 phosphorylation was inhibited by FK506 and C3. Conclusions- Mechanical stretch-induced VSMC hypertrophy and leptin synthesis and secretion is mediated by Ca2+/calcineurin/NFAT activation. RhoA/ROCK and ERK1/2 activation are critical for mechanical stretch-induced calcineurin activation.